Public Catering Enterprises: Analysis and Prospects of Innovative Development - Larisa A. Mayurnikova; Arkadiy A. Koksharov; Tatyana V. Krapiva; Anna I. Petkovich; Vladislav O. Meshkov (Техника и технология пищевых производств)
Public catering has become an important healthy food provider in Russia. As a rule, this sphere is represented by small businesses with no experience in innovation. Their prospects for innovative development depend on the form of ownership, size, and target audience. The present research objective was to develop recommendations on how to restructure a public catering enterprise as part of an innovative development strategy. The study featured public catering enterprises together with their innovative potential, activities, and factors that contribute to or hinder their development. The innovative restructuring scenarios were based on the synthesis method. The authors developed a goal-centered classification which includes commercial and socially oriented public catering enterprises with their own advantages and disadvantages. The list of disadvantages includes decentralization, overstaffing, and multi-format, which make it difficult to introduce innovations and strategizing. The restructuring process requires a new management system optimized by specialists competent in the field of innovation, as well as a new matrix of strategic resources. An audit of public catering enterprises makes it possible to assess their competitiveness and strategic prospects. The current lack of personnel with experience in innovations hinders the development of the industry. Universities and regional innovation infrastructure should provide public catering with specialists in innovation management. Keywords